2009
DOI: 10.1364/oe.17.007285
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive monitoring of cerebral blood oxygenation in ovine superior sagittal sinus with novel multi-wavelength optoacoustic system

Abstract: Noninvasive monitoring of cerebral blood oxygenation with an optoacoustic technique offers advantages over current invasive and noninvasive methods. We report the results of in vivo studies in the sheep superior sagittal sinus (SSS), a large central cerebral vein. We changed blood oxygenation by increasing and decreasing the inspired fraction of oxygen (FiO(2)). Optoacoustic measurements from the SSS were performed at wavelengths of 700, 800, and 1064 nm using an optical parametric oscillator as a source of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…15 The oxygenated blood that subsequently flows into the veins may lead to HbT and SO 2 increases. 2,36 The current fPAM system found that the times to peak HbT and SO 2 were shorter in the MI arterioles than in veins under different stimulation intensities. To transfer a significant amount of HbT and SO 2 into the activation region, shorter times are needed to reach peak HbT and SO 2 in MI arterioles than in veins.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…15 The oxygenated blood that subsequently flows into the veins may lead to HbT and SO 2 increases. 2,36 The current fPAM system found that the times to peak HbT and SO 2 were shorter in the MI arterioles than in veins under different stimulation intensities. To transfer a significant amount of HbT and SO 2 into the activation region, shorter times are needed to reach peak HbT and SO 2 in MI arterioles than in veins.…”
Section: Discussionmentioning
confidence: 92%
“…To transfer a significant amount of HbT and SO 2 into the activation region, shorter times are needed to reach peak HbT and SO 2 in MI arterioles than in veins. 15,36,37 Moreover, the greater increases in the HbT and SO 2 levels also indicate increased CBF. 32 This finding of dissociation of the HbT and CBV responses strongly suggests that Grubb's relationship between CBF and CBV [CBV ¼ 0.8 × CBF (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive measurement of other important physiologic variables 1,2 including total hemoglobin concentration can be performed as well, because infants (in particular, LBW and VLBW infants) often have abnormal levels of total hemoglobin concentration. We developed, built, and tested in animal and clinical studies optoacoustic systems for noninvasive measurement and continuous monitoring of cerebral oxygenation and other important physiologic variables [3][4][5][6][7][8][9][10][11][12][13][14] . The optoacoustic technique combines the advantages of both optical (high contrast) and ultrasound (high resolution) techniques and (using well-established difference in the absorption spectra of oxy-and deoxyhemoglobin 15 ) can be used for accurate monitoring of cerebral oxygenation and other important physiologic variables in adults, children, and infants.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used optoacoustics to monitor blood oxygenation in the SSS of adult humans, 14 neonates, 15 and sheep, 11,13 as well as in the human IJV. 12…”
Section: Introductionmentioning
confidence: 99%